ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DI DESA BAJO KECAMATAN TILAMUTA KABUPATEN BOALEMO - Sri Hantuti Paramata; Nur Eng Mokodompit; Rosdiana Zees (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This research was conducted with the aim of determining the extent of the welfare level of the fisherman community in Bajo Village, Tilamuta District, Boalemo Regency and also to determine the level of inequality or Gini ratio in Bajo Village. The type of research in this thesis is to use a simple random sampling technique with a population of 120 people and a sample of 24 respondents. Primary data was obtained by means of direct interviews with respondents. Analysis of the data used is a table analysis of the distribution of the questionnaire. The results of the research were analyzed from all welfare indicators based on BPS indicators in 2015 that the welfare level of Bajo Village, Tilamuta District, Boalemo Regency was still low with the number of respondents 13 respondents from 24 respondents, meaning that Bajo Village, Tilamuta District, Boalemo Regency was still classified as not prosperous. From the results of the analysis, it can be concluded the level of inequality in the expenditure of the fishing community is classified as high with a Gini value of 0.65.